Absolute calibration of the Colour and Stereo Surface Imaging System (CaSSIS). (February 2022) - Thomas, Nicolas; Pommerol, Antoine; Almeida, Miguel; Read, Matthew; Cremonese, Gabriele; Simioni, Emanuele; Munaretto, Giovanni; Weigel, Thomas
Abstract: The Colour and Stereo Surface Imaging System (CaSSIS) onboard the ExoMars Trace Gas Orbiter (TGO) has observed several standard stars and Jupiter with the aim of deriving the absolute calibration factors that convert observed signal into reflectance ("I over F"). The targets were observed through all four colour filters and hence a relative calibration between the filters was possible. In addition, observations of Phobos acquired during the TGO capture orbits in 2016 were analysed in support of the relative colour calibration. The results show that CaSSIS was around 13% less sensitive than predicted (normalised to the RED filter) - a value that is larger than the formal uncertainty and therefore significant. The relative colour calibration shows CaSSIS to be 4% more sensitive in the BLU than modelled which is close to the relative uncertainty. The text describes the analysis approach and methods for the various targets and newly recommended conversion factors are provided in table form. Graphical abstract: Image 1 Highlights: The Colour and Stereo Surface Imaging System (CaSSIS) on the ExoMars TGO is a photometrically precise instrument. Various astronomical objects have been used to determine the absolute response to an observed radiance. Conversion factors from digital numbers to I/F are provided to an estimated accuracy of approximately 3%.